Embodying Progress: Aesthetic Surgery and Socioeconomic Change in South Korea. Issue 1 (1st March 2016) - Albrecht, Eduardo Zachary
Abstract : Since the early 1960s South Korea has had one of the fastest-growing economies in the world. These developments have had a deep impact on the structure of society, but what impact have they had on the body? This article examines the relationship between such rapid socioeconomic transformations and the changes in uses and perceptions of the physical body among Koreans. This article uses a phenomenological theoretical framework to look at the narratives of embodiment of young Koreans that have had experiences with aesthetic surgery. The research examines the hypotheses that (1) the rapid transformations occurring in the South Korean economy are partly enabled by a specific ideology—a kind of ideology of progress in which economic productivity is valued above other aspects of everyday life, and (2) this ideology is articulated in the way individuals view and manage their bodies. In particular, it is evident in the embodied practices of Korean youths, such as the relatively recent popularization of aesthetic surgery. Thus, through surgical technologies the body is made to be more economically "productive" and may better contribute to the progress of the country as a whole.